PENGARUH PENERAPAN MODEL PEMBELAJARAN INOVATIF PICTURE AND PICTURE TERHADAP MINAT DAN HASIL BELAJAR IPS SISWA KELAS V SDN 1 LALEBBATA KOTA PALOPO - Sapinah .; Muh. Yahya; Suryani . (STKIP Pembangunan Indonesia Makassar, 2019)
This study aims to: To find out: 1. The influence of the application of the Picture and Picture Innovative learning model on the interest in learning social studies subjects of Class V SDN 1 Lalebbata Palopo City. 1. Influence of the application of Innovative Picture and Picture learning models on the learning outcomes of Social Studies students of Grade V SDN 1 Lalebbata Palopo.This research is a quantitative type of experimental research, with a research design with treatment through preetes and posttes. The study population was 100 class V students. The sample of this study were 68 students. The results showed that: Based on the results of the calculation of the Independent Samples Test students' interest in learning social studies in the out put obtained the value of Sig. (2-tailed) of 0.002 <0.05, it can be concluded that there is a difference between the average student learning interest between control groups and experiment. The results of the calculation of Independent Samples Test results of students' social studies learning in Table 4.5, the out put obtained the Sig. (2-tailed) value of 0.000 <0.05, then according to the basis of decision making in the indevendent test Sample T-test can be concluded that there is a difference between the average learning outcomes of control and experimental groups Keywords: Innovative Picture and Picture learning model, interest, learning Result